Lead and Juvenile Delinquency: New Evidence from Linked Birth, School, and Juvenile Detention Records - Aizer, Anna; Currie, Janet (The Review of Economics and Statistics, 2019)
Using a unique data set linking preschool blood lead levels, birth, school, and detention records for 125,000 children born between 1990 and 2004 in Rhode Island, we estimate the impact of lead on school suspension and juvenile detention. Sibling fixed-effect models suggest that omitted variables related to family disadvantage do not bias OLS estimates. However, measurement error does. We use IV methods that exploit local (within-neighborhood), variation in lead exposure deriving from road proximity and the deleading of gasoline. For boys, a 1 unit increase in lead increased the probability of suspension from school by 6% and detention by 57%.